PENGARUH ORIENTASI SERAT PADA KOMPOSIT KAIN POLYPROPYLINE - Muhammad Ariyansah; Achmad Kusairi Samlawi (JTAM ROTARY, 2019)
The purpose of this research is to know the effect of fiber orientation variation on tensile strength and impact strength on polypropyline fabric composite. In this study the reinforcing materials used were polypropyline fabrics with variations of fiber orientation 0º:-45º:0 ; 0:45º:0º ; and 0º:90:0º using unsaturated polyester resin 108 as the matrix. Preparation by hand lay up, impact testing conducted with reference standard ASTM D5942-96 and tensile testing conducted with reference ASTM D638-03 standard. The test results showed that the variation with 0°:90°:0° orientation gave the best effect to the impact test and tensile test with the impact price of 128,66 Joule / cm² and tensile strength of 98,49 MPa. Keywords: Polypropyline, Composite, Impact Strength, Tensile Strength